Malnutrition in Surgical Wards: A Plea for Concern - Offir Ben-Ishay; Haya Gertsenzon; Tanya Mashiach; Yoram Kluger; Irit Chermesh (Gastroenterology Research and Practice)
Background. Malnutrition in hospitalized patients is underdiagnosed, with 30 to 60% of patients admitted being malnourished. The objective of this study was to investigate the nutritional status of patients in a general surgery ward and to define the correlation between the risk of malnutrition and the hospital course and clinical outcome. Study design. The study group included 100 consecutive patients admitted to a general surgery ward who were ambulant and could undergo the Malnutrition Universal Screening Tool (MUST). Results. Thirty-two patients (33%) had aMUST score of 2 or higher, and were therefore defined at high-malnutrition risk. The patients at risk had longer hospitalization and worse outcome. The length of stay of the malnourished patients was significantly longer than that of patients without malnutrition risk (18.8 ± 11.5 vs. 7 ± 5.3 days, 𝑃=.003). Mortality in the high-risk group was higher overall, in hospital, and after six months and one year of followup. Conclusions. Medical personnel must be aware that malnutrition afflicts even patients whose background is not suggestive of malnutrition. Best results are achieved when cooperation of all staff members is enlisted, because malnutrition has severe consequences and can be treated easily.